SYNTHESIS AND BIOLOGICAL PROPERTIES OF PHARMACEUTICALLY IMPORTANT XANTHONES AND BENZOXANTHONE ANALOGS: A BRIEF REVIEW. - Bedi, Pooja; Gupta, Richa; Gupta, Richa; Pramanik, Tanay; Pramanik, Tanay (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Xanthones are one of the biggest classes of compounds in natural product chemistry. A number of xanthones have been isolated from natural sources of higher plants such as fungi, ferns, and lichens. Synthetic analogs of xanthones have shown a large number of pharmacological properties such as antioxidant, anti-inflammatory, antidiabetics, antihistamine, antitumoral, antiulcer, and algicidal. Moreover, they also find usages in photodynamic therapy, laser technology, and dyes. This review lays stress on various solvents, catalyst and synthetic route for synthesis of xanthones, benzoxanthones analogs. The review has also focused on the classifications of xanthone as well as extensively studied biological properties of the xanthones and benzoxanthones analogs.